Quercetin as a possible complementary agent for early-stage COVID-19: Concluding results of a randomized clinical trial - Di Pierro, Francesco; Khan, Amjad; Iqtadar, Somia; Mumtaz, Sami Ullah; Chaudhry, Muhammad Nabeel Akbar; Bertuccioli, Alexander; Derosa, Giuseppe; Maffioli, Pamela; Togni, Stefano; Riva, Antonella; Allegrini, Pietro; Recchia, Martino; et al. (Frontiers in Pharmacology, 2023)
Background: Quercetin, a natural polyphenol with demonstrated broad-spectrum anti-viral, anti-inflammatory, and antioxidant properties, has been proposed as an adjuvant for early stage COVID-19 infection. Objective: To explore the possible therapeutic effect of quercetin in outpatients with early-stage mild to moderate symptoms of COVID-19. Methods: This was an open-label randomized controlled clinical trial conducted at the department of medicine King Edward Medical University, Lahore, PK. Patients were randomized to receive either standard of care (SC) plus quercetin (oral 500 mg Quercetin Phytosome®, 1st week, TDS: 2nd week, BDS) (n=50, quercetin group) or SC alone (n=50, control group). Results: After one week of treatment, patients in the quercetin group showed a speedy recovery from COVID-19 as compared to the control group, i.e; 34 patients (vs 12 in the control group) tested negative for SARS-CoV-2 (p=0.0004), and 26 patients (vs 12 in the control group) had their COVID-19-associated symptoms resolved (p=0.0051). Patients in the quercetin group also showed a significant fall in the serum lactate dehydrogenase (LDH) mean values i.e; from 406.56 ± 183.92 to 257.74 ± 110.73 U/L, p=0.0001. Quercetin was also well-tolerated, with no side effects. Conclusions: Our results, suggest the possible therapeutic role of quercetin in early-stage COVID-19, including speedy clearance of SARS-CoV-2, early resolution of the acute symptoms and modulation of the hyperinflammatory response.